Measuring Religious Maturity: A Proposed Scale - Dudley, Roger L. (Review of religious research, 1990)
Gordon Allport offered a rich and complex description of mature religion. More recently, Batson and Ventis have proposed that the scales constructed to measure Allport's intrinsic orientation actually capture only part of the concept of maturity that he had in mind--religion as master motive. They have offered the quest orientation to account for the qualities of complexity, humility, and tentativeness. But quest seems as one-sided as intrinsic. In an attempt to construct a scale that would reflect the religious maturity Allport originally envisioned, a pool of items were written; combined with intrinsic, extrinsic, and quest items into the Personal Religion Inventory, and administered to 491 subjects. The resulting factor analyses produced the 11-item Religious Maturity Scale. It is offered as a further tool with which to test theory and conduct new research on personal orientations to religion.